PlGF knockdown attenuates hypoxia-induced stimulation of cell proliferation and glycolysis of lung adenocarcinoma through inhibiting Wnt/β-catenin pathway - Wei Zhang (Cancer Cell International, 2021)
Abstract Background Angiogenic placental growth factor (PlGF) plays a role in hypoxia-induced angiogenesis. Here, we aimed to investigate the biological roles of PlGF in cell proliferation and glycolysis of lung adenocarcinoma (LUAD) and the underlying molecular mechanisms. Methods PlGF was knocked down in H358 and H1975 cells by lentiviruses, which were then cultured under hypoxia (90% N2, 5%CO2 and 5%O2) for 24 h. PlGF was overexpressed in PC9 cells treated with XAV939, inhibitor of Wnt/β-catenin signaling pathway. PlGF-silencing H1975 cells were implanted into mice, and tumor xenografts were harvested and analyzed. Results Hypoxia treatment led to up-regulation of PlGF, C-myc, lactate dehydrogenase A (LDHA), and β-catenin, promotion of cell proliferation and glycolysis in H358 and H1975 cells, which were obviously reversed by knocking down PlGF. In tumors, PlGF knockdown significantly prohibited cell proliferation and glycolysis, and decreased expression of C-myc, LDHA, and β-catenin. PlGF overexpression markedly strengthened cell proliferation, which was inhibited by β-catenin knockdown. Consistently, XAV939, inhibitor of Wnt/β-catenin pathway, also inhibited PlGF-induced cell proliferation, glycolysis, and β-catenin expression in PC9 cells. Conclusion PlGF knockdown inhibited the stimulatory effect of hypoxia on cell proliferation and glycolysis of LUAD through deactivating Wnt/β-catenin pathway.